The impact of materialistic monism and suffering on medical students :a critique of the biomedical and biopsychosocial model of medical schools - Kuehne, Jan (Jan Cavan) (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--University of Stellenbosch, 2007.